2018
DOI: 10.1038/s41377-018-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

A fiber optoacoustic guide with augmented reality for precision breast-conserving surgery

Abstract: Lumpectomy, also called breast-conserving surgery, has become the standard surgical treatment for early-stage breast cancer. However, accurately locating the tumor during a lumpectomy, especially when the lesion is small and nonpalpable, is a challenge. Such difficulty can lead to either incomplete tumor removal or prolonged surgical time, which result in high re-operation rates (~25%) and increased surgical costs. Here, we report a fiber optoacoustic guide (FOG) with augmented reality (AR) for sub-millimeter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Beyond imaging, recent advances in developing optoacoustic materials have enabled highly efficient optoacoustic conversion 27 . Pulsed light excitation of these optoacoustic materials generates ultrasound waves at high amplitude, which allowed for all-optical ultrasound imaging 28,29 , tissue cavitation 30,31 , and precision surgical guidance of lumpectomy 32 .…”
mentioning
confidence: 99%
“…Beyond imaging, recent advances in developing optoacoustic materials have enabled highly efficient optoacoustic conversion 27 . Pulsed light excitation of these optoacoustic materials generates ultrasound waves at high amplitude, which allowed for all-optical ultrasound imaging 28,29 , tissue cavitation 30,31 , and precision surgical guidance of lumpectomy 32 .…”
mentioning
confidence: 99%
“…Similarly, Noimark et al [ 30 ] and Poduval et al [ 31 ] coated CNTs and subsequently PDMS on the tip of an optical fiber and showed peak frequency of 20 MHz and 30 MHz, with bandwidth of 23∼40 MHz and 29 MHz, respectively. In our previous work, an optical fiber coated with ZnO/Epoxy and Graphite/Epoxy was developed, serving as an optoacoustic guide for sub-millimeter tumor localization and intuitive surgical guidance [ 32 ]. To study the involvement of cochlear pathway in the ultrasound induced brain stimulation, the fiber based optoacoustic emitter was used for spatially confined neuron stimulation of mouse brain in vivo [ 33 ], showing powerful capability of understanding the bio-interface mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…2 With advances in laser, instrumentation, and algorithms, PA imaging has become a multiscale imaging tool from microscopic to macroscopic domains. [3][4][5] Apart from numerous imaging applications, the PA effect has been recently utilized as a versatile ultrasonic source for ultrasound (US) imaging, 6 tissue localization, 7 ablation, 8 and neuromodulation. 9 Nevertheless, the dissipation limit of photons in a tissue fundamentally prevents PA applications over 7 cm in depth, at which photons are diminished to none by the strong tissue scattering.…”
Section: Introductionmentioning
confidence: 99%